2006
DOI: 10.1186/bf03352673
|View full text |Cite
|
Sign up to set email alerts
|

Imaging S-wave scatterer distribution in southeast part of the focal area of the 2005 West Off Fukuoka Prefecture Earthquake (MJMA 7.0) by dense seismic array

Abstract: Spatial distribution of S-wave scatterers in the SE part of the focal area of the 2005 West Off Fukuoka Prefecture Earthquake (M = 7.0) has been estimated using dense seismic array data. Waveforms of 22 natural earthquakes were analyzed in a frequency range of 16-24 Hz. It is difficult to estimate the inhomogeneous structure in this wavelength range with ordinary travel time tomography despite the importance of this parameter for understanding the earthquake-generating process. After filtering and gain recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It relates to the inelastic deformation around the area, suggesting possibility that the medium is heterogeneous there. Matsumoto et al [2006, 2009] revealed that the relative scattering strength and attenuation factor of seismic waves are high around the edge of the fault. Their results demonstrate that the medium in the region also has inelastic property and/or strong heterogeneity with the shorter wavelength than wavelength of the seismic wave around 4–30 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…It relates to the inelastic deformation around the area, suggesting possibility that the medium is heterogeneous there. Matsumoto et al [2006, 2009] revealed that the relative scattering strength and attenuation factor of seismic waves are high around the edge of the fault. Their results demonstrate that the medium in the region also has inelastic property and/or strong heterogeneity with the shorter wavelength than wavelength of the seismic wave around 4–30 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 12(c), the scatterer distribution reported by Matsumoto et al (2006) is shown. Based on seismic array observations, they identified relatively strong scatterers using array processing that determines coherent waves in the coda part, yielding the distribution.…”
Section: Discussionmentioning
confidence: 96%
“…The white contour denotes the slip distribution proposed by Asano & Iwata (2006). (c) Scatterer distribution estimated by Matsumoto et al (2006) based on the seismic array observation. The shaded area denotes the value with low reliability.…”
Section: Discussion Smentioning
confidence: 99%